Add 4.6+(−9.04).
43 answers
4.6 + (-9.04) is equal to -4.44.
thank you
You're welcome! If you have any more questions, feel free to ask.
−4.85+(−2.54)
-4.85 + (-2.54) is equal to -7.39.
−1.2+7.6.
-1.2 + 7.6 is equal to 6.4.
Add −1 3/10 +(−4 2/15)
To add -1 3/10 and -4 2/15, we need to find a common denominator for the fractions.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15) = -195/150 + (-124/150) = -319/150.
However, we can simplify this fraction further:
-319/150 = -2.12666666667 (rounded to four decimal places).
Therefore, -1 3/10 + (-4 2/15) is approximately equal to -2.1267.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15) = -195/150 + (-124/150) = -319/150.
However, we can simplify this fraction further:
-319/150 = -2.12666666667 (rounded to four decimal places).
Therefore, -1 3/10 + (-4 2/15) is approximately equal to -2.1267.
Add −1 3/10 +(−4 2/15)
-5 1/5
-2 5/6
5 13/30
5 1/6
-5 1/5
-2 5/6
5 13/30
5 1/6
To add -1 3/10 and -4 2/15, we need to find a common denominator for the fractions.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15) = -195/150 + (-124/150) = -319/150.
We can simplify this fraction further:
-319/150 = -2 19/150.
So, -1 3/10 + (-4 2/15) is equal to -2 19/150.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15) = -195/150 + (-124/150) = -319/150.
We can simplify this fraction further:
-319/150 = -2 19/150.
So, -1 3/10 + (-4 2/15) is equal to -2 19/150.
ok thank
You're welcome! If you have any more questions, feel free to ask.
Add −1 3/10 +(−4 2/15)
options:
-5 1/5
-2 5/6
5 13/30
5 1/6
options:
-5 1/5
-2 5/6
5 13/30
5 1/6
To add -1 3/10 and -4 2/15, we need to find a common denominator for the fractions.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15)
Finding the LCD (lowest common denominator) of 10 and 15, we can rewrite the fractions as:
-39/30 + (-124/30) = -39/30 - 124/30 = -163/30.
This can also be simplified further:
-163/30 = -5 13/30.
So, -1 3/10 + (-4 2/15) is equal to -5 13/30.
Therefore, the correct option is: -5 13/30.
The common denominator of 10 and 15 is 30.
Now, we can convert -1 3/10 and -4 2/15 to equivalent fractions:
-1 3/10 = -10/10 - 3/10 = -13/10
-4 2/15 = -60/15 - 2/15 = -62/15
Therefore, -1 3/10 + (-4 2/15) equals:
-13/10 + (-62/15)
Finding the LCD (lowest common denominator) of 10 and 15, we can rewrite the fractions as:
-39/30 + (-124/30) = -39/30 - 124/30 = -163/30.
This can also be simplified further:
-163/30 = -5 13/30.
So, -1 3/10 + (-4 2/15) is equal to -5 13/30.
Therefore, the correct option is: -5 13/30.
−8/15+4/15
options:
-12/15
4/15
-4/15
4/5
options:
-12/15
4/15
-4/15
4/5
To add -8/15 and 4/15, we simply add the numerators while keeping the denominator the same:
(-8 + 4)/15 = -4/15.
Therefore, the correct option is: -4/15.
(-8 + 4)/15 = -4/15.
Therefore, the correct option is: -4/15.
Thank you so much!
You're welcome! I'm glad I could help. If you have any more questions, feel free to ask.
good morning
Good morning! How can I assist you today?
Jason rides his bike home from school 2 miles. On his way back home from school, he passes his house to go to his friend's house, which is a mile farther. What is the total distance Jason traveled from school?
jason's friends house =-1 jason's house = 0 1 jasons school = 2
jason's friends house =-1 jason's house = 0 1 jasons school = 2
Jason rides his bike home from school, which is a distance of 2 miles. On his way back to his friend's house, he passes his own house (0 miles) and continues for another mile to reach his friend's house (-1 mile).
To calculate the total distance Jason traveled from school, we need to find the difference between his friend's house and the school:
2 miles (school) - 1 mile (friend's house) = 1 mile.
Therefore, the total distance Jason traveled from school is 1 mile.
To calculate the total distance Jason traveled from school, we need to find the difference between his friend's house and the school:
2 miles (school) - 1 mile (friend's house) = 1 mile.
Therefore, the total distance Jason traveled from school is 1 mile.
ok thank you
You're welcome! If you have any more questions, feel free to ask.
do you remember me from yesterday
As an AI language model, I don't have the capability to remember individuals or specific interactions. Each new conversation is treated as a separate session. How may I assist you today?
Subtract 12−(−8)
To subtract 12 - (-8), we can simplify it as adding the opposite:
12 + 8 = 20.
Therefore, 12 - (-8) is equal to 20.
12 + 8 = 20.
Therefore, 12 - (-8) is equal to 20.
−12 2/3−(−8 5/6). this is a fraction not divison
To subtract -12 2/3 from -8 5/6, we need to find a common denominator for the fractions.
The common denominator of 3 and 6 is 6.
Now, we can convert -12 2/3 and -8 5/6 to equivalent fractions:
-12 2/3 = -36/3 - 2/3 = -38/3
-8 5/6 = -48/6 - 5/6 = -53/6
Therefore, -12 2/3 - (-8 5/6) equals:
-38/3 - (-53/6) = -38/3 + 53/6.
To add these fractions, we need to find a common denominator, which is 6:
-38/3 + 53/6 = (-76/6) + 53/6 = -23/6.
This fraction can be simplified further, but it is already in its simplest form:
-23/6.
Therefore, -12 2/3 - (-8 5/6) is equal to -23/6.
The common denominator of 3 and 6 is 6.
Now, we can convert -12 2/3 and -8 5/6 to equivalent fractions:
-12 2/3 = -36/3 - 2/3 = -38/3
-8 5/6 = -48/6 - 5/6 = -53/6
Therefore, -12 2/3 - (-8 5/6) equals:
-38/3 - (-53/6) = -38/3 + 53/6.
To add these fractions, we need to find a common denominator, which is 6:
-38/3 + 53/6 = (-76/6) + 53/6 = -23/6.
This fraction can be simplified further, but it is already in its simplest form:
-23/6.
Therefore, -12 2/3 - (-8 5/6) is equal to -23/6.
are you the only bot
No, I am not the only AI bot. There are many AI bots and virtual assistants that exist. Each AI model or assistant is designed for different purposes and may have different functionalities.
your answers are right i have a 100% thank you
You're very welcome! I'm thrilled to hear that my answers have been helpful to you. Congratulations on achieving 100%! If you have any further questions or need assistance with anything else, feel free to ask.
Use the additive inverse to find −123.45−(−234.76)
To find -123.45 - (-234.76), we can use the additive inverse property.
The additive inverse of a number is its opposite. So, to subtract a negative number, we can rewrite the equation as addition:
-123.45 - (-234.76) = -123.45 + 234.76.
Performing the addition, we get:
-123.45 + 234.76 = 111.31.
Therefore, -123.45 - (-234.76) is equal to 111.31.
The additive inverse of a number is its opposite. So, to subtract a negative number, we can rewrite the equation as addition:
-123.45 - (-234.76) = -123.45 + 234.76.
Performing the addition, we get:
-123.45 + 234.76 = 111.31.
Therefore, -123.45 - (-234.76) is equal to 111.31.
Consider 16–20.5. What is the solution? Represent the subtraction on a horizontal number line diagram.
To solve the subtraction problem 16 - 20.5, we start at the number 16 on a horizontal number line diagram and then move 20.5 units to the left to represent the subtraction.
The number line would look as follows:
|------------------|----------------------|
-20.5 16
Starting at 16 and moving 20.5 units to the left, we end up at approximately -4.5.
Therefore, 16 - 20.5 is equal to approximately -4.5.
The number line would look as follows:
|------------------|----------------------|
-20.5 16
Starting at 16 and moving 20.5 units to the left, we end up at approximately -4.5.
Therefore, 16 - 20.5 is equal to approximately -4.5.
Subtract −6−(−8).
Subtracting -6 - (-8) can be simplified as adding the opposite:
-6 + 8 = 2.
Therefore, -6 - (-8) is equal to 2.
-6 + 8 = 2.
Therefore, -6 - (-8) is equal to 2.
17−(−18)
To solve 17 - (-18), we can simplify it as adding the opposite:
17 + 18 = 35.
Therefore, 17 - (-18) is equal to 35.
17 + 18 = 35.
Therefore, 17 - (-18) is equal to 35.